Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah Tabungan Britama Pada Bank BRI Cabang Fatmawati - Viva Faronika; Asriyal Asriyal (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2012)
If the customer is greater than acceptable level of service, the cutomer is not satisfied. Conversely, if an acceptable level of service greater than the expectations of customers, the customer will be satisfied. This means that if Bank BRI branch Fatmawati can improve service quality to its customer it will affect the level of satisfaction. In this research found evidence that, in terms of the creation of quality services, Bank BRI branch Fatmawati is one of the branches that participate to implement the established policies and service in accordance with the exiting service standard in the banking world. Amount of influence the determination of quality of service policies applied by the Bank BRI branch Fatmawati indicated by r2. r2 value only 45 % and the rest 55 % influenced by other variables not studied. Meanwhile, the variable relationship of service quality to customer satisfaction can be seen from the values r = 0,67. This shows the value of the correlation coefficient between the variables of service quality to customer satisfaction. This means there are strong relationships between the independent variable X (quality of service) to the dependent variable Y (customer satisfaction). Since r = 0,67 (67 %) greater then 50 %.